In vivo Modulatory Effect of Clerodendrum Splendens (Glory Blossom) in Aluminum Induced Alzheimer Diseases and Lonchocarpus Sericeus in Rotenone Induced Parkinson’s Disease on Na+/K+ Atpase (Sodium Pump) in the Cerebral Tissues of Male Albino Wister Rats - Umoh Esther Udo; Dibua Redeemed Ihimoya; Ojo Oluwabukola (International Journal of Biochemistry and Biomolecule Research, 2023)
Elegant research has shown that plants are useful for both curative and preventive purpose on the humans populous. Prevalent among diseases associated with humans are neurological diseases which affect a large sector of the population especially the elderly. The most common neurological diseases are Parkinson and Alzheimer disease which affect a large sector of the brain and also cause an imbalance in brain electrolyte. Among such electrolytic mechanisms of the brain are those which regulate the inflow an out flow of sodium and potassium levels in the cerebral tissue and the system responsible for such is the sodium pump. This is a p type ATPase which controls the influx and out flux of sodium and potassium ions in the brain and whose damage can trigger a lot of neurological problems. Due to the important of this “pump”, this research was aimed at examining the modulatory effect of two plants species (Clerodendrum Splendens and Lonchocarpus sericeus) on sodium potassium ATPase in the cerebral tissue of mammals. Methodologies employed in this research are the Na+/K+ ATPase by Svoboda and Mosinger, 1981. All results were estimated at P<0.05. It is interesting to know that result obtained from this research shows that there was no significant different in the sodium potassium ATPase level in group three and four of both groups. However, as compared to the positive control, the sodium potassium ATPase level was higher and to the negative and standard, it almost obtained 100% efficiency. This implies that Clerodendrum Splendens and Lonchocarpus sericeus have great impact on restoring the sodium potassium ATPase activity in the cerebral tissue of Alzheimer and Parkinson disease patients and may also serves as a medicament in treating other neurological disorders.
Keywords: Alzheimer and Parkinson; cerebral tissue; neurological disease